JAMINAN PERLINDUNGAN HUKUM TERHADAP PEKERJA/BURUH YANG MELAKSANAKAN HAK MOGOK DI INDONESIA - Chairina Nopiyanti Sipahutar; Budiman Ginting; Pendastaren Tarigan; Agusmidah Agusmidah (USU LAW JOURNAL, 2017)
ABSTRACT A strike is the basic right for employees/laborers which has to be protected by law. It has to be performed legally, orderly, and peacefully. The problems of the research were whether there was the relevance of a permit to go on strike to the implementation of the strike as the basic right of employees/laborers, whether law on Workforce provided legal protection for employees/laborers that went on strike, and whether there was legal constraint faced by them in going on strike. The research used judicial normative method by using primary, secondary, and tertiary legal materials. The data were gathered by conducting library research and analyzed qualitatively. Law on Workforce regulates legal strike in which, in its implementation, it is limited by complicated permit requirements and procedures for employees/laborers in going on legal strike. These complicated requirements and procedures become legal constraints for employees/laborers in struggling for their aspiration. However, Law on Workforce has many loopholes in the regulations on strike. Legal protection and the prohibition for the termination of employment and wages which should be paid during the strike are intended for those who go on strike legally. However, legal protection is only given to employees/laborers as far as they are on strike legally which is almost impossible to be done.  Based on the result of the research, it is recommended that law makers improve and complete the substance of the legal provisions which still have many loopholes. Besides that, in the future, the implementation of strike should prioritize the substance of the strike which is the basic right for employees/laborers to express their petition rather than fulfill formal requirements and the procedure of permit in carrying out strike.   Keywords: Legal Protection, Right to Go on Strike, Strike Permit.